PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE PADA PEMBELAJARAN TEMATIK KELAS III SDN 17 PONTIANAK KOTA - Maulana, Dio Vialli; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
AbstrakThis study aimed to develop an independent learning of media in the form of an application with SWF (Small Web File) extension and can be opened via Android. This study used the research and development (RnD) method by adapting the Borg and Gall model. The data of this study were taken from student questionnaire sheets as well as the results of interviews with the third grade elementary school teachers of State Secondary school Number 17, Pontianak City. The results showed that during the process of the development of   thematic-based independent learning, students have been through 7 of stages in learning: the potential and problem stages, data collection, product design, design validation, design revision, product testing, and product revision. The feasibility of this learning media in the first phase of the trial showed that   94%   responses of students lead to very decent criteria. Meanwhile, in the second trial, the response of students showed that the response from students was 96% having very decent criteria.KeywordsAdobe Flash Professional CS6, Development, Self Learning Media, Thematic